Solar Energy as an Approach for Sustainable Architecture of Residential Buildings in Egypt - Mostafa Abd elhafeez; Dina Noaaman; Ashraf EL-Mokadem (Port Said Engineering Research Journal, 2012)
For the optimal use of solar energy (SE) in residential buildings and achieving sustainability for it , the paper is done about, energy consumption in the residential sector, renewable energy (RE), sustainability and basic design issues affecting it, and  systems used in assessing the sustainability, access to the barriers that hinder RE to achieve sustainability in residential buildings. Study SE as one of the most important sources of RE to reach the residential energy producing building which led to the need to a new look of the building. Analysis and evaluation of government policies, programs, legislation and construction codes used in leader countries to exploit SE in achieving the sustainability of residential buildings, with analyzes case studies of the successful international experiences in this area and the extent of its success in achieving sustainability relying on SE, and the effect of the techniques used to shape and design of the residential building, and the effect of solar education, funding, design factors,  legislation and construction codes, and government policies on the success of these experiments. Study the possibilities of Egypt in the field of RE, and the use of technology in achieving sustainability of residential buildings. With studing the current status and attempts of Egypt experiences tried to increase the contribution of SE in total energy mix in residential sector as a prerequisite to achieving sustainability of the sector, and the study result  access to a strategy to encourage the use of SE in residential buildings in Egypt to achieve sustainability